The Effectiveness of Platelet-Rich Plasma in Reducing Pain and Improving Functional Outcomes for Patients with Knee Osteoarthritis: A Systematic Review - Millsep Sieroka; Sherrina Oktaviani Gosandra (The International Journal of Medical Science and Health Research, 2025)
INTRODUCTION Knee osteoarthritis (KOA) is a leading cause of global disability, characterized by chronic pain and functional decline. Current intra-articular therapies, such as corticosteroids and hyaluronic acid, offer limited or transient benefits. Platelet-rich plasma (PRP), an autologous concentration of growth factors, has emerged as a biological therapy with the potential to modulate the joint environment. This systematic review aims to synthesize the highest-level evidence on the effectiveness of intra-articular PRP for reducing pain and improving function in patients with KOA. METHODS This review was conducted following PRISMA guidelines. A comprehensive search of PubMed, Google Scholar, Semanthic Scholar, Springer, and Wiley Online Library was performed to identify randomized controlled trials (RCTs) comparing intra-articular PRP with placebo (saline), hyaluronic acid (HA), or corticosteroids (CS) for symptomatic KOA. Primary outcomes were changes in the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and Visual Analogue Scale (VAS) for pain. A broad range of secondary outcomes, including KOOS, IKDC, Lequesne Index, quality of life scores, and adverse events, were also assessed. Methodological quality was evaluated using the Cochrane Risk of Bias 2.0 tool. RESULTS The analysis included evidence from numerous RCTs comprising thousands of patients. The results demonstrate a distinct temporal pattern of efficacy for PRP. Compared to placebo, HA, and CS, PRP injections provide statistically and clinically significant improvements in pain and function, with benefits becoming most pronounced at mid- to long-term follow-up (6 to 12 months). Network meta-analyses consistently rank PRP as the most effective injectable therapy for sustained improvement. Efficacy is greatest in patients with mild-to-moderate KOA (Kellgren-Lawrence grades I–III), and leukocyte-poor PRP formulations appear to yield superior outcomes. PRP is safe, with the most common adverse events being minor, transient local reactions like pain and swelling. DISCUSSION The synthesized evidence indicates that the primary advantage of PRP over traditional injectables is the durability of its clinical benefit, which aligns with its proposed biological, disease-modulating mechanism of action rather than a purely palliative effect. However, the clinical applicability of these findings is challenged by significant heterogeneity across studies in PRP preparation protocols, injection schedules, and patient populations. This lack of standardization, coupled with methodological limitations in the primary literature, tempers the overall certainty of the evidence. CONCLUSION Intra-articular PRP is a safe and effective treatment for KOA, offering superior and more durable pain relief and functional improvement compared to HA and CS, particularly for patients with early-to-moderate disease. Standardization of PRP formulation and treatment protocols is critical to optimize outcomes and establish its definitive role in the clinical management of KOA.